2020
DOI: 10.1002/rcm.8856
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic and elemental corroborates for wild bearded capuchin (Sapajus libidinosus) omnivorous dietary adaptation at Fazenda Boa Vista, Brazil

Abstract: Rationale This study analyzes variability in the diets of wild bearded capuchin monkeys, Sapajus libidinosus, by analyzing stable carbon (δ13C) and nitrogen (δ15N) isotope ratios and elemental concentrations (%C and %N) of fecal samples and food items. Developing isotopic and elemental correlates for diets of habituated subjects is a necessary step towards applying similar methods to interpret diets of unhabituated or cryptic subjects. Methods Fecal samples from wild capuchins and their foods were collected at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
8
2
Order By: Relevance
“…Fecal %C, %N, δ 13 C, and δ 15 N values do not differ significantly between the one infant, as well as juveniles older than 2.7 years old, and their mothers (Figure 4). Therefore, Hypothesis 4 (isotopic effect of breastfeeding) was not supported in this study, though several previous studies showed a systematic increase in %N, δ 13 C, and δ 15 N values in breastfed infants of chimpanzee and langur (B adescu et al, 2017, 2022Reitsema, 2012; but see Reitsema et al, 2020).…”
Section: Orangutan Fecescontrasting
confidence: 75%
See 1 more Smart Citation
“…Fecal %C, %N, δ 13 C, and δ 15 N values do not differ significantly between the one infant, as well as juveniles older than 2.7 years old, and their mothers (Figure 4). Therefore, Hypothesis 4 (isotopic effect of breastfeeding) was not supported in this study, though several previous studies showed a systematic increase in %N, δ 13 C, and δ 15 N values in breastfed infants of chimpanzee and langur (B adescu et al, 2017, 2022Reitsema, 2012; but see Reitsema et al, 2020).…”
Section: Orangutan Fecescontrasting
confidence: 75%
“…Fecal %C, %N, δ 13 C, and δ 15 N values do not differ significantly between the one infant, as well as juveniles older than 2.7 years old, and their mothers (Figure 4 ). Therefore, Hypothesis 4 (isotopic effect of breastfeeding) was not supported in this study, though several previous studies showed a systematic increase in %N, δ 13 C, and δ 15 N values in breastfed infants of chimpanzee and langur (Bădescu et al, 2017 , 2022 ; Reitsema, 2012 ; but see Reitsema et al, 2020 ). Behavioral and trace elemental studies showed that breastfeeding continues ~7 years after birth in wild orangutans (Mendonça et al, 2017 ; Smith et al, 2017 ; van Noordwijk et al, 2009 , 2013 ; van Noordwijk & van Schaik, 2005 ), and orangutan infant/juveniles investigated in this study, aged from 2.7 to 6.5 years, are expected to consume breast milk.…”
Section: Discussioncontrasting
confidence: 62%
“…Obtaining measurements of milk transfer, and thus of lactation effort for mothers, is a formidable challenge, but meeting this challenge is key to understanding how growth, development and reproduction are linked in mammalian life history evolution (Sellen 2006). Measuring milk synthesis directly and non-invasively in the wild is not currently feasible for most mammals, but stable isotope analyses of urine and feces provide indirect means to assess aspects of diets and of when, and to what extent, infants include foods other than milk in their diets (Liden and Angerbjorn 1999;Codron et al 2006;Oelze et al 2011;Blumenthal et al 2012;Reitsema et al 2015Reitsema et al , 2020Bădescu et al 2016Bădescu et al , 2017Loudon et al 2016;Schoeninger et al 2016). Several studies have used stable nitrogen isotopes in feces to calculate δ 15 N values for infant mammals.…”
Section: Measuring Lactation Effort Using Stable Nitrogen (δ 15 N) Is...mentioning
confidence: 99%
“…Several studies have used stable nitrogen isotopes in feces to calculate δ 15 N values for infant mammals. These values reflect nitrogen in the amino acids of dietary proteins; thus, they detect an individual's trophic position and can quantify the relative dietary contributions of maternal milk to non-milk foods in infant diets (Reitsema 2012;Bădescu et al 2016Bădescu et al , 2017Reitsema et al 2020). For infants of mammal species utilizing mostly or entirely plant-based diets, infants' δ 15 N values provide information about infant daily protein intake (Reitsema 2012;Bădescu et al 2017), and thus about how much of the protein in their diets comes from milk (an animal source).…”
Section: Measuring Lactation Effort Using Stable Nitrogen (δ 15 N) Is...mentioning
confidence: 99%
“…Although some studies have attempted to correlate measures of time spent suckling with estimates of infant reliance on maternal milk (see the review by Cameron 1998) and with isotopic methods (Eumetopias jubatus: Higgins et al 1988;Equus caballus: Cameron et al 1999), the approach that we have adopted here builds on literature combining isotopic and behavioural data to study maternal strategies (e.g. Cameron et al 1999;Bădescu et al 2016;Bădescu et al 2017;Reitsema et al 2020;Bădescu et al 2022), and indicates how these two types of data can be combined in wild populations to provide a more complete picture of the weaning process.…”
Section: Population-level Weaning Dynamicsmentioning
confidence: 99%